Investigations on mechanical properties of jute fiber and epoxy resin composites with titanium oxide. (2022) - Preethi, M.S.; Ramya, C.H.; Sumathi, G.; Mounika, N.; Sateesh, N.
Abstract: The composite material is made up of a combination of materials with distinct chemical and physical properties. The utilization of jute fiber and epoxy resin composites is very extensive in the fields of aircraft and automobiles. These composites have a huge strength-to-weight ratio. Even so, modern applications require a significant increase in strength. The addition of Nano fillers had resulted in considerable changes in the mechanical properties of the composite. The present work aims at finding out the effects on mechanical properties of composites due to the addition of titanium oxide. The specimens are prepared for tensile testing and hardness testing according to the ASTM standards by Hand Layup process with the combinations of jute fiber and epoxy resin. The composite is prepared by three variables with (0%, 5%, 10%)filler and three orientations (0°-90°, 45°-45°, random). The specimens are tested on the Universal Testing Machine of model UTE-10 and shore hardness-'A' the comparison process is laid down.